A Multivariate Assessment of Age-Related Cognitive Impairment in Octodon degus - Rivera, Daniela S.; Lindsay, Carolina B.; Oliva, Carolina A.; Bozinovic, Francisco; Inestrosa, Nibaldo C. (Frontiers in Integrative Neuroscience, 2021)
Aging is a progressive functional decline characterized by a gradual deterioration of physiological function and behavior. The most important age-related changes in cognitive function are decline in cognitive performance (processing or transformation of information to make decisions, working memory, and learning). The purpose of this study is to outline the changes in age-related cognitive performance (short-term recognition memory and long-term learning and memory) in the long-lived Octodon degus. The strong similarity between degus and humans in social, metabolic, biochemical, and cognitive aspects, makes it a unique animal model for exploring the mechanisms underlying the behavioral and cognitive deficits related to natural aging. In this study, we examined young adult female degus (12- and 24-months old) and aged female degus (38-, 56- and 75-months old) that were exposed to a battery of cognitive-behavioral tests. Multivariate analyses of data from the Social Interaction test or Novel Object/Local Recognition (to measure short-term recognition memory), and the Barnes maze test (to measure long-term learning and memory), revealed a consistent pattern. Young animals formed a separate group of aged degus for both, short and long-term memory. The association between the first component of the PCA from short-term memory with the first component of the PCA from long-term memory showed a significant negative correlation. This suggests age-dependent differences in both memories, with aged degus having higher values of long-term memory ability, but poor short-term recognition memory, whereas in young animals an opposite pattern was found. Approximately 5% of young and 80% of aged degus showed impaired short-term recognition memory. Whereas, for the long-term memory about 32% of young animals and 57% of aged degus showed decreased performance on the Barnes maze test. Throughout this study, we outline age-dependent cognitive performance decline during natural aging in degus. Moreover, we also demonstrated that the use of a multivariate approach lets us explore and visualize complex behavioral variables, and identify specific behavioral patterns that allow us to make powerful conclusions that will facilitate further the study of the biology of aging. In addition, this work could help to predict the onset of the aging process based on behavioral performance.